2023
DOI: 10.5194/esurf-11-305-2023
|View full text |Cite
|
Sign up to set email alerts
|

The story of a summit nucleus: hillslope boulders and their effect on erosional patterns and landscape morphology in the Chilean Coastal Cordillera

Abstract: Abstract. While landscapes are broadly sculpted by tectonics and climate, on a catchment scale, sediment size can regulate hillslope denudation rates and thereby influence the location of topographic highs and valleys. In this work, we used in situ 10Be cosmogenic radionuclide analysis to measure the denudation rates of bedrock, boulders, and soil in three granitic landscapes with different climates in Chile. We hypothesize that bedrock and boulders affect differential denudation by denuding more slowly than t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that outcropping bedrock can erode at a smaller rate than surrounding loose material in a catchment (e.g Bierman and Caffee, 2001;Heimsath et al, 2006;Lodes et al, 2023). We may wonder if this difference can affect the estimation of the mean scarp erosion rate from the 10 Be concentration in colluvium.…”
mentioning
confidence: 99%
“…It has been shown that outcropping bedrock can erode at a smaller rate than surrounding loose material in a catchment (e.g Bierman and Caffee, 2001;Heimsath et al, 2006;Lodes et al, 2023). We may wonder if this difference can affect the estimation of the mean scarp erosion rate from the 10 Be concentration in colluvium.…”
mentioning
confidence: 99%